2023
DOI: 10.7717/peerj-cs.1333
|View full text |Cite
|
Sign up to set email alerts
|

Graph data science and machine learning for the detection of COVID-19 infection from symptoms

Abstract: Background COVID-19 is an infectious disease caused by SARS-CoV-2. The symptoms of COVID-19 vary from mild-to-moderate respiratory illnesses, and it sometimes requires urgent medication. Therefore, it is crucial to detect COVID-19 at an early stage through specific clinical tests, testing kits, and medical devices. However, these tests are not always available during the time of the pandemic. Therefore, this study developed an automatic, intelligent, rapid, and real-time diagnostic model for the early detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Predicting the clinical progression of patients with severe COVID-19 is very important because patients can present post-acute sequelae such as kidney and heart infections, liver failure and compromised lung function ( 40 ). Long COVID is tightly associated with the severe cases of COVID-19 as well as the clinical management of patients during the acute phase of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Predicting the clinical progression of patients with severe COVID-19 is very important because patients can present post-acute sequelae such as kidney and heart infections, liver failure and compromised lung function ( 40 ). Long COVID is tightly associated with the severe cases of COVID-19 as well as the clinical management of patients during the acute phase of disease.…”
Section: Discussionmentioning
confidence: 99%
“…The training process of the node classification pipeline implemented in [ 61 ] was applied to detect influenza and hepatitis diseases in this study as indicated in Algorithm 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Hybrid models concatenate different combinations of ML and DL models at different model architecture levels [96,101,102]. Graph models reflect the underlying logical connection of the model components in a graphical style [103,104]. Graph neural networks (GNNs) are novel graph models that comprise input variables as graph components, e.g., nodes and edges.…”
Section: Model Trainingmentioning
confidence: 99%